JUVENILE HYALINE FIBROMATOSIS - Krishnamurthy, Jayashree (Medknow Publications & Media Pvt Ltd, 2011)
Juvenile hyaline fibromatosis is a rare, autosomal-recessive disease characterized by papular and nodular skin lesions, gingival hyperplasia, joint contractures and bone involvement in variable degrees. It is a connective tissue disorder with aberrant synthesis of glycosaminoglycans by fibroblasts. We report a 5-year-old female born of first-degree consanguineous marriage who presented with multiple, recurrent, painless, variable-sized nodules. Fine needle aspiration cytology smears and the subsequent histopathological examination from the nodules showed benign spindle cells in a Periodic acid Schiff-positive myxoid background. The disease has a relentlessly progressive course, with most patients surviving only up to the 4(th) decade. As of now, there is no specific treatment for this disorder. Genetic counseling is essential to explain to parents about a 25% chance of having a diseased baby in any pregnancy. With the gene being mapped recently, techniques for antenatal diagnosis are likely to be established.